The Utilizing Powtoon Learning Videos in Civics Learning in Fourth Grade Elementary School - Salsabila Rissa Nugraheni; Achmad Fathoni (Universitas Pendidikan Ganesha, 2022)
Conventional learning using blackboard media reduces students' interest in participating in learning activities. Therefore it is necessary to integrate technology to increase student interest in learning activities. This study aimed to analyze the effectiveness of audiovisual Powtoon media in increasing student learning interest in PKN subjects in elementary schools. The method used is an experimental method with a pre-experimental design in the form of a one-group pretest-posttest design. The research subjects were fourth-grade elementary school students. The average pretest result of student interest in learning is 65.17, while the average posttest result of student interest in learning is 77.86. The results showed that using Powtoon learning videos effectively increased students' interest in civic education subjects. The calculation results use the effect size formula of 1.08. The effect of using Powtoon learning audiovisual media on increasing student interest is very high. This research implies that Powtoon media can be used as a learning tool to increase student's interest and motivation significantly.